Evaluation of research projects: Perspectives for applied research in food and agriculture - Pedersen, S.M.; Boesen, M.V.; Baker, Derek; Larsen, A.; Pedersen, J.L. (Informa UK Limited, 2011)
In this study, the task of evaluating research projects’ relevance and scientific quality is addressed, and a pilot study is executed for five Danish food and agricultural research programmes. Literature reviewed emphasises the importance of context, of consistency and transparency and of the cost of evaluation. Moreover, the purpose of research evaluation is thoroughly examined. The method developed and implemented addresses each of these concerns, particularly by employing simple measures and by complementing quantitative analysis with qualitative exercises featuring structured stakeholder interviews. The results of the pilot indicate substantial variation between projects within programmes, and some evidence of size-performance relationships.